P4_5 A Rogue Earth - Rowe, Ryan; Byworth, Kayleigh; Garner, James; Lawrence-Morgan, Dennis (Physics Special Topics, 2022)
The Earth decides a giant mirror would be the best defence against the Death Star’s laser. Due to the conservation of momentum, when the mirror reflects the laser the mirror’s velocity and hence the Earth’s velocity must increase to 0.9998617325c. This will result in the Earth escaping from the Sun’s gravitational pull and becoming a rogue planet.As a result, this strategy would be infeasible as the destruction of everyone on planet Earth would still be guaranteed.